Effect of polyelectrolyte interlayer on efficiency and stability of p-i-n perovskite solar cells. (1st December 2016) - Yang, Haifeng; Zhang, Jincheng; Zhang, Chunfu; Chang, Jingjing; Lin, Zhenhua; Chen, Dazheng; Sun, Xu; Xi, He; Han, Genquan; Hao, Yue
Graphical abstract: Highlights: A high performance perovskite solar cell with the PEIE interlayer is demonstrated. The obviously enhanced uniformity for the devices with PEIE interlayer are achieved. The PEIE layer can suppress the trap-assisted recombination for the devices. The stability of the corresponding device is also improved. Abstract: In this work, we demonstrated a high performance planar heterojunction perovskite solar cell with the polyethylenimine ethoxylated (PEIE) interlayer. By adopting a less polar solvent for PEIE, enhanced device performance and uniformity are achieved. The power conversion efficiency (PCE) of the best device increases by 22% compared to the reference device and reaches 14.82% with JSC of 19.45 mA/cm 2, VOC of 1.00 V, and FF of 76.31% under AM 1.5G 100 mW/cm 2 light illumination. The UPS measurement shows that the PEIE layer can effectively decrease the energy offset between PCBM and metal electrode. The recombination mechanism was explored by measuring VOC and JSC at various light intensities from 100 to 0.1 mW/cm 2 . It shows that the PEIE layer can suppress the trap-assisted recombination for the devices. The enhancement of the probability of the carriers collection also shows that the recombination is reduced by the PEIE interlayer. Moreover, it is found PEIE layer can improve the stability of the device.